COVID-19 Vaccine Acceptance in Pregnant and Lactating Women and Mothers of Young Children in Poland - Kuciel N; Mazurek J; Hap K; Marciniak D; Biernat K; Sutkowska E (Dove Medical Press, 2022)
Natalia Kuciel,1 Justyna Mazurek,1 Katarzyna Hap,1 Dominik Marciniak,2 Karolina Biernat,1 Edyta Sutkowska1 1University Centre of Rehabilitation, Wroclaw Medical University, Wroclaw, Poland; 2Department of Drugs Form Technology, Wroclaw Medical University, Wroclaw, PolandCorrespondence: Katarzyna Hap, University Centre of Rehabilitation, Wroclaw Medical University, Borowska St. 213, Wroclaw, Poland, Tel +48/717343220, Email katarzyna.hap@umw.edu.plPurpose: The World Health Organization indicated vaccine hesitancy as one of the top 10 threats to global health. The success of a vaccine depends not only on its efficacy but also on its acceptance. Our study aims to define COVID-19 vaccine acceptance in a sample of pregnant and lactating women in Poland. Since mothers are often key decision-makers for whether their children will receive vaccination, it is vital to measure vaccine confidence among this group.Patients and Methods: An anonymous online survey was distributed to assess the level of acceptance of COVID-19 vaccination among pregnant and lactating women for themselves and their children in Poland.Results: The trust of pregnant and breastfeeding women and women who have offspring in government, in healthcare professionals, in scientific authorities, and sound scientific data is strongly associated with vaccine acceptance and may influence an individual's decision to perceive recommended actions as beneficial to the society as a whole.Conclusion: Acceptance and confidence in receiving the COVID-19 vaccination among pregnant and lactating women and mothers with young children is strongly associated with feelings of trust in government, health professionals, scientific authorities, and sound scientific data. The dissemination of professional and reliable information regarding the safety and efficacy of COVID-19 vaccine uptake by qualified health care personnel can significantly increase the level of trust and public awareness regarding the safety and efficacy of COVID-19 vaccine uptake in pregnancy, while breastfeeding, and mothers with young children.Keywords: COVID-19, vaccination, breastfeeding, pregnancy, acceptance of vaccination